2010
DOI: 10.1021/la100774q
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Diffusion, and Permeability of Protein-Stabilized Monodispersed Oil in Water Emulsions and Their Gels: A Self-Diffusion NMR Study

Abstract: Self-diffusion NMR is used to investigate monodispersed oil in water emulsions and the subsequent gel formed by removing the water through evaporation. The radius of the oil droplets in the emulsions is measured using a number of diffusion methods based on the measurement of the mean squared displacement of the oil, water, and tracer molecules. The results are consistent with the known size of the emulsions. Bragg-like reflections due to the restricted diffusion of the water around the oil droplets are observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…It is directly related to different physical parameters such as the size and shape of the diffusing particle, the temperature, and the viscosity of the solution. It can be characterized by a diffusion tensor D, the trace of it being the diffusion coefficient D. It is a parameter characteristic of the nature and properties of liquids, solutions, and gels [63,64]. Thus it allows access to properties, such as molecular volume and/or weight, mobility and dynamic behavior, and chemical interactions with their environment.…”
Section: H Nmr Dosymentioning
confidence: 99%
“…It is directly related to different physical parameters such as the size and shape of the diffusing particle, the temperature, and the viscosity of the solution. It can be characterized by a diffusion tensor D, the trace of it being the diffusion coefficient D. It is a parameter characteristic of the nature and properties of liquids, solutions, and gels [63,64]. Thus it allows access to properties, such as molecular volume and/or weight, mobility and dynamic behavior, and chemical interactions with their environment.…”
Section: H Nmr Dosymentioning
confidence: 99%
“…While the first minimum is well modelled, the second minimum is not predicted. This has previously been observed when characterising monodisperse emulsions with radii from 12 to 20 µm [136], and is attributed to the model not accounting for diffusion of the molecules beyond the first shell of pores [135,136].…”
Section: Continuous Phase Diffusionmentioning
confidence: 64%
“…Romoscanu et al [82] have fitted NMR data to this model for an oil-in-water emulsion with droplet size around 35 μm, and showed that this method has a high ability to predict the emulsion structure. This model was established for glassy spherical beads with rigid surfaces, hence the dynamics of the interface are not taken into account, resulting in deviation of the model at high q-value [77].…”
Section: -1-1-2 Size Probing: Pore Hopping Analysismentioning
confidence: 99%
“…This model was established for glassy spherical beads with rigid surfaces, hence the dynamics of the interface are not taken into account, resulting in deviation of the model at high q-value [77]. Romoscanu et al [82] claimed that the oil droplet size and structure information can be extracted from the extrema of the model.…”
Section: -1-1-2 Size Probing: Pore Hopping Analysismentioning
confidence: 99%
See 1 more Smart Citation